Student evaluation at Windhoek College of Education: Evidence of quality assurance to improve teaching and learning (Journal for Studies in Humanities and Social Sciences, 2015)
Using a qualitative approach, this paper took a critical look at the role of student evaluation at the then Windhoek College of Education as a tool to assess the quality of teaching at the institution. It examined the pros and cons of introducing student evaluation as a tool to measure teaching effectiveness of academic staff at this institution. The findings showed that, despite the fact that literature reveals that student evaluation is a common tool used to assess the content pedagogy of academic staff in many institutions worldwide, there are concerns that need to be taken into consideration in terms of validating the outcomes of these evaluations. The findings show that these concerns include: student lecturer relationship; student interest in a particular subject; lecturer subject content and pedagogical skills; general appearance of the lecturer; lecturer’s assertiveness and the quality of training received. It concludes by affirming that dealing with people’s perceptions and attitude is a complex phenomenon, and, in the context of this research, there was a need for a paradigm shift in the way lecturers at the former Windhoek College of Education perceived student evaluations vis-à-vis its purpose in academia.